Impact of recipient body mass index on heart transplantation outcomes - Masroor, Matiullah; Jiang, Chen; Xiong, Tixiusi; Wang, Yixuan; Dong, Nianguo (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveObesity is one of the common risk factors for heart failure. Heart transplantation (HTx) is a gold standard treatment option for end-stage heart failure. The relationship between obesity and HTx outcomes is not very clear. This study aims to investigate the impact of recipient BMI on heart transplantation outcomes.MethodsFrom 2012–2021, 821 patients underwent HTx in our center. Patients with age less than 18 years, multiorgan transplantation, re-transplantation, and missing recipient BMI data were excluded. The remaining 694 patients were divided into four BMI categories based on the recipient's BMI value. BMI < 18.5 kg/m2 (n = 70), BMI 18.5–24.99 kg/m2 (n = 432), BMI 25–29.99 kg/m2 (n = 156), and BMI ≥ 30 kg/m2 (n = 36). Analysis of variance and chi-square test with post hoc test according to the types of variables was performed to find differences among the groups. Kaplan–Meier analysis with a Log-rank test was performed for the survival analysis. Cox regression analysis was performed to adjust for confounders and see the effect of variables on mortality.ResultsSome preoperative variables, such as recipient gender and diabetes status, were statistically significantly different between the groups. However, there was no significant difference in the postoperative outcomes except for high intra-aortic balloon pump (IABP) use in the BMI ≥ 30 kg/m2 group based on unadjusted analysis. The Kaplan–Meier survival analysis showed no short or long-term survival difference between the groups. The 5-year survival was 75%, 70%, 71%, and 83% in underweight, normal weight, overweight, and obese recipient BMI groups, respectively. Recipient BMI was not associated with follow-up mortality on multivariable analysis. Preoperative IABP use, history of chronic kidney disease, and recipient age were the independent risk factors for long-term mortality. The risk of mortality was five times higher in patients with preoperative IABP use and two times higher in patients with a history of CKD. A one-year increase in recipient age was associated with a 3.4% increase in mortality risk.ConclusionThe recipient BMI did not significantly impact post-transplantation survival after multivariable adjustment. However, unadjusted analyses showed comparable non-survival outcomes across BMI groups. Our study suggests that selected underweight and class I obese patients may undergo heart transplantation without increased risk of post-transplantation mortality.